A mitopoética amazônica nas percepções de discentes numa escola da agrovila de São Raimundo em Castanhal - PA - ALVES, Jefferson da Silva (2020)
This work aims to understand the Amazon mythopoetics in the students perceptions in a school of the São Raimundo agroforestry in Castanhal, it is configured as a qualitative approach, through the application of semi-structured interviews with: 02 teachers from the São Raimundo, 03 former teachers of the community, 05 residents in the age group of 25 to 80 years. In addition to informal conversations with some students of the school of São Raimundo. We use the authors: Loureiro (2001, 2005), Severino (2007), Lakatos and Marconi (2009), Brandão (2002), Cruz (2013), Brazil (1988, 1996, 2010), Durand (2012), Bachelard (1988), Rocha (1996), Pinheiro (2018) among others to Provide theoretical basis. The results of the research allowed to know better the profile of respondents and their culture.